Being a Myeloproliferative Patient in COVID-19 Era: The Mytico Study - Cavalca, Fabrizio; Renso, Rossella; Zambrotta, Giovanni Paolo Maria; Gambacorti-Passerini, Carlo; Elli, Elena Maria (Frontiers in Oncology, 2021)
Introduction: The Coronavirus disease 2019 (COVID-19) pandemic and the resulting social distancing, determined a reduction in access to care and limitations of individual freedom, with a consequent strong impact on quality of life (QoL), anxiety levels and medical management of onco-hematological people. In particular, in the case of patients with chronic myeloproliferative neoplasm (MPN), concern about SARS-CoV-2 infection added to the burden of symptoms (BS) which already weights on the QoL of these patients. We designed a cross-sectional survey in order to investigate the impact of the COVID-19 pandemic on status of anxiety, BS and QoL in MPN patients. Methods: We analyzed the anxiety levels using the Zung Self-Rating Anxiety Scale (SAS); BS modifications were studied using the 18 items of the Myeloproliferative Neoplasm Symptom Assessment Form [MPN-SAF]. Results: 132 people answered to the survey: 27 (20.4%) patients achieved a marked to severe anxiety index value: this group described a greater worsening of symptoms than the rest of the cohort (p <0.0001). Women showed a higher level of anxiety than men (p = 0.01). A trend for lower level of anxiety was reported by patients who performed habitual physical activity (p = 0.06). A total of 98 (74.2%) patients described worsening of their symptoms during the quarantine period; 94 (71.2%) patients had postponed appointments or visits: they showed a significant worsening of their BS (p =0.01). Conclusion: This study first showed that the COVID-19 quarantine had a significant negative impact on the level of anxiety and BS in MPN patients. We identified female gender, absence of physical activity, the need for frequent visit to the hospital and the absence of a direct access to healthcare staff as the main factors associated to a higher anxiety index and worst BS.